An Empirical Study on the Influence of Students’Awareness on the Brand Identity: A Case of Telkom University Indonesia - Sari Wulandari (International Journal of Innovation in Enterprise System, 2017)
Mergers made by IT Telkom and other higher education institutions such as IM Telkom, Telkom Polytechnic and STISI Telkom, have an impact on IT Telkom brand image. IT Telkom together with these institutions created a new brand name of Telkom University. The Brand of Telkom University uses a different brand identity from previous brand identity. The use of this new brand identity affects brand awareness and brand image of the previous brand of IT Telkom. This research is conducted to find out the people’s brand awareness of IT Telkom merger. The numbers of sample are 781 respondents. Data processing was performed using Chi - Square test. The results indicated that awareness of this mergers influences perceptions of competence and brand reputation, awareness of vision, mission, and motto affect all brand identity, and awareness of the logo affects the perception related to the relevance of brand identity as a whole. Keywords—Merger, University, Awareness, Brand Identity